Reunion [large type] : a novel - Snelling, Lauraine (Center Point Publishing, 2012)
Keira Johnson, a 50-year-old mother of two grown sons, believes she lives a good Christian life without secrets -- until she discovers a life-jarring fact her late mother kept hidden all her life. Kiera was born out of wedlock, and the man she had always known as her father had adopted her as an infant. Meanwhile, Keira's beloved 17-year-old niece, Kirsten, has just discovered an unwanted pregnancy. Her boyfriend, Jose, is bound for college and Kirsten does not know what to do. As the family comes together for a reunion, Keira and Kirsten struggle with their fractured pasts and jumbled present. Will truth and honesty be the catalysts that allow the entire family to find peace? Inspired by events in Lauraine Snelling's own life.